Model Dynamic Pricinguntuk Penetapan Harga Tiket Pesawat Terbang Berbasis Waktu dan Persediaan Kursi dengan Mempertimbangkan Keputusan Kompetitor - Ahmad Rusdiansyah; Rescha Dwi A. P.; Nia Puspitasari (Institute of Research and Community Outreach - Petra Christian University, 2013)
In the airline business nowadays the competition between airlinesis very tight. The decision of pricing of an airline will affect significantly the demand and revenue of other airlines. This study develops a model of Airline Revenue Management (ARM). We build an ARM model under competitive environment. The model considers the change of the competitor’s ticket for two parallel flights and should be made based on time and seat inventory. Specifically, we develop a model of dynamic programming to obtain the optimal ticket price based on the remaining seats, the rest of the time, as well as changes in competitors' ticket prices in order to generate maximum revenue expectation. This study conducted a series of numerical experiment scenarios to demonstrate the behavior of the model to the revenue expectation.